Qualidade da Água e do Sedimento de Corpos Hídricos do Município de Alegre, Espírito Santo - Firmino, Elziane Favoreto Alves (2018)
The agricultural activity uses a great amount of agrochemicals for the guarantee and increase of its productivity. However, this practice affects the environment, especially the quality of water bodies. The persistence of agrochemicals in the environment